ANALISIS KEPUASAN SISWA TERHADAP KEGIATAN PEMBELAJARAN BIOLOGI PADA SEKOLAH FORMAL DAN LEMBAGA BIMBINGAN BELAJAR NON-FORMAL DI KOTA MADIUN - Sigit Ari Prabowo; Muh. Waskito Ardhi; Joko Widiyanto (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2015)
To achieve national education purpose, Indonesia's government provide three categories facilities, formal, non-formal, and informal education. Formal education held the Ministry of education, non-formal education organized independently, informal education in family and society. Three types education work together to achieve the national education purpose. The research purposeto determine students satisfaction level to learning Biology in formal school and non-formal learning. Analysis results of research are expected as material evaluation Organizer formal education in order to meet the needs student learning without having to rely institutions of the mentorship of non-formallearning. Research using observation method, researchers conducted bservations directly the research object to see the reality in the field. Data collected using questionnaires on 30 respondents high level school students. Questionnaire were analyzed using comparative average student learning satisfaction in formal school and non-formal learning. Student learning satisfaction measurementresults on the quality of the material, 81,6% of formal schooling and non-formal learning 87,6% , aspects method of formal school 87% and non-formal learning 75%, teaching quality aspects of formal school 79% and non-formal learning 83%, school formal infrastructure aspects of 92% and non-formal learning 76%, learning time aspects formal school 90% and non-formal learning 85%.